Development of the bitales application to improve students' local wisdom-based digital literacy - Arif Akbar; Ita Fitriati; Ahyar Ahyar; Sitti Suhada; Arif Rahman Hakim (Jurnal Inovasi dan Teknologi Pembelajaran)
Digital-based learning that integrates local wisdom is rarely implemented in Bima, including at SMPN 1 Palibelo. Based on findings in the field, learning at this school still uses a traditional approach without utilizing technology to introduce local culture. This research aims to develop the Bima Tales (BiTales) application based on Android as a digital literacy medium that combines folklore and local wisdom values typical of Bima. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the media expert validity test showed a "Good" category with an average score of 4.43, while the material expert gave an average score of 4.46. The app proved effective in improving students' digital literacy and understanding of local wisdom, as seen from the increase in learning outcomes from an average pretest score of 50.48 to 77.62 in the post-test and understanding of local wisdom from 41.19 to 75.95. This research shows that the integration of digital technology with local cultural content can improve the quality of learning and strengthen students' cultural identity.